ASSESSMENT OF OPTIMUM YIELD OF GROUNDWATER WITHDRAWAL IN THE YOGYAKARTA CITY, INDONESIA - Doni Prakasa Eka Putra; Muhammad Iqbal; Heru Hendrayana; Thomas Triadi Putranto (Journal of Applied Geology, 2015)
The high demand of clean water supply and groundwater usages in Yogyakarta City, Indonesia has caused the lowering of groundwater table of about 3 m in average since 1984. This condition is caused by the increase number of groundwater pumping in this city relate to the rising of the urban population, economics condition, education and cultural activities, change of land use and increase number of hotels on this famous tourism city in Indonesia. Therefore, it became necessary to assess the optimum yield from the groundwater system beneath this city which can still preserve the recent level of shallow groundwater. This is important because most of the people in this city depends their daily water supply from shallow dug well. In order to assess the safe yield, a groundwater modeling is conducted. The data used on this modeling was taken from previous research and also primary data collected during this research such as; aquifer geometry, aquifer characteristics, shallow groundwater level, water usage/pumping wells discharge, river discharge and surface water level, and climate data. Prediction of the impact of groundwater pumping was made by increasing the water usage/pumping wells discharge on several scenarios. The result of this modeling shows that the optimum yield of the aquifer beneath Yogyakarta City area is about 125,000 m3/day. Keywords: Optimum yield, groundwater usage, groundwater table, pumping, urban population, shallow dug well.